2022
DOI: 10.1177/0271678x211069266
|View full text |Cite
|
Sign up to set email alerts
|

Aging related impairment of brain microvascular bioenergetics involves oxidative phosphorylation and glycolytic pathways

Abstract: Mitochondrial and glycolytic energy pathways regulate the vascular functions. Aging impairs the cerebrovascular function and increases the risk of stroke and cognitive dysfunction. The goal of our study is to characterize the impact of aging on brain microvascular energetics. We measured the oxygen consumption and extracellular acidification rates of freshly isolated brain microvessels (BMVs) from young (2–4 months) and aged (20–22 months) C57Bl/6 male mice. Cellular ATP production in BMVs was predominantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Recently, it was reported that oxidative phosphorylation also played an important role in endothelial cells. Sakamuri et al reported that cellular ATP production in isolated brain microvessels was predominantly dependent on oxidative phosphorylation (Sakamuri et al, 2022). Wilson et al reported that mitochondrial ATP generated in endothelial cells was necessary for calcium‐dependent, nitric oxide mediated endothelial control of vascular tone (Wilson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that oxidative phosphorylation also played an important role in endothelial cells. Sakamuri et al reported that cellular ATP production in isolated brain microvessels was predominantly dependent on oxidative phosphorylation (Sakamuri et al, 2022). Wilson et al reported that mitochondrial ATP generated in endothelial cells was necessary for calcium‐dependent, nitric oxide mediated endothelial control of vascular tone (Wilson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Age and senescence related decreases in glycolysis and OXPHOS have previously been reported in BMECs suggesting that MCMV infection may accelerate an aging phenotype relative to mock infected animals (Sakamuri et al, 2022). Uncoupling of the ETC may explain the increased proton leak and play a protective role by mitigating ROS production and therefore oxidative damage (Divakaruni and Brand, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…In this regard, some investigators have used metabolic flux analysis to show that isolated brain capillaries (composed mostly of ECs) primarily use oxidative phosphorylation. 89 RNA sequencing of freshly isolated single ECs is also increasingly being used, without a cell culture step, to characterize endothelial metabolic signatures. 90 , 91 Such studies reveal a diversity of metabolic profiles (mitochondrial and glycolytic) amongst ECs of various organs.…”
Section: Discussionmentioning
confidence: 99%